2022
DOI: 10.5577/intdentres.2022.vol12.no2.3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold drinks on the coloration of resin-containing restorative materials

Abstract: Aim: Resin-containing restorative materials are widely used in the restoration of teeth. Our aim in this study is to examine the color change of beverages consumed cold on resin-containing restorative materials. Methodology: Samples were prepared using composite resins and resin-based CAD/CAM blocks. All prepared samples were kept in cold tea, cold coffee, coke, energy drink, and distilled water after polishing. The color values of the samples were measured with a spectrophotometer at the beginning, on the 1st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(36 reference statements)
0
1
1
Order By: Relevance
“…The findings disagreed with (36,(42)(43)(44)(45)(46)(47)(48)(49)(50) , who reported that Emax CAD, Vita Suprinity or Vita Enamic showed clinically acceptable color change (ΔE) following immersion in coffee. This may be due to difference in methodology regarding technique used for sample preparation, ceramic brands, ceramic thickness, immersion time, immersion technique and immersion solution brands or concentration.…”
Section: Discussioncontrasting
confidence: 65%
“…The findings disagreed with (36,(42)(43)(44)(45)(46)(47)(48)(49)(50) , who reported that Emax CAD, Vita Suprinity or Vita Enamic showed clinically acceptable color change (ΔE) following immersion in coffee. This may be due to difference in methodology regarding technique used for sample preparation, ceramic brands, ceramic thickness, immersion time, immersion technique and immersion solution brands or concentration.…”
Section: Discussioncontrasting
confidence: 65%
“…There was no statistically significant difference in color changes of the resin containing dental materials at the end of the 1st day (p > 0.05) but, at the end of the 7th and 30th day, cold tea caused statistically higher color change (p < 0.05). Composite resins showed more color change than resin-based CAD/CAM blocks [39]. Alfouzan AF (2021) evaluated and compared the color stability of 3D-printed and conventional heat-polymerized acrylic resins following aging, mechanical brushing, and immersion in staining medium.…”
Section: Discussionmentioning
confidence: 99%